Pengaruh Brand Experience Dan Online Customer Review Terhadap Kepuasan Konsumen Pada Familymart Cabang Wolter Monginsidi Kota Jakarta Selatan - Laela Desiani; Nani Nani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of Brand Experience and Online Customer Reviews on Consumer Satisfaction at FamilyMart Wolter Monginsidi branch, South Jakarta. The research method used is quantitative. The sampling technique uses the Rao Purba formula with a sample size of 96 respondents. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The results show that Brand Experience and Online Customer Reviews have a significant effect on Consumer Satisfaction with the regression equation Y = 2.737 + 0.182 (X1) + 0.320 (X2). The correlation coefficient (R) value of 0.749 indicates a strong relationship between the independent variable and the dependent variable. The coefficient of determination (R2) value of 0.560 or 56% indicates the contribution of the influence of the independent variable on the dependent variable, while the remaining 44% is influenced by other factors not examined in this study. Partially, the Brand Experience hypothesis test produces a calculated t value of 7.094> t table 1.985 so that H0 is rejected and H1 is accepted, which means there is a significant influence of Brand Experience on Consumer Satisfaction. The partial test of Online Customer Review produces a calculated t value of 10.091> t table 1.985, so that H0 is rejected and H2 is accepted, which means there is a significant influence of Online Customer Review on Consumer Satisfaction. The results of the F test show a calculated F value of 59.278> F table 2.700 with a significance value of 0.000 <0.05. Thus, it can be concluded that Brand Experience and Online Customer Review simultaneously have a significant influence on Consumer Satisfaction.